FACTORS ASSOCIATED WITH SOCIAL PARTICIPATION ACCORDING TO RESIDENCE AREA AMONG ELDERLY IN INDONESIA - Ulfa, Laila; Sartika, Ratu Ayu Dewi; Kusharisupeni, . (PEOPLE: International Journal of Social Sciences, 2019)
Social participation in elderly is an important component of active aging. The purpose of this study was to identify factors associated with social participation in elderly by differential residence area (urban/rural). This cross-sectional study involved all subjects (n = 2900) aged ≥ 60 years old from Indonesia Family Life Survey data (IFLS) 2014. Chi-square analysis were used to identify factors associated with social participation. This study found that the proportion of social participation in elderly in urban area was greater than rural. Factors associated with social participation both in rural and urban areas were level of education and working status.According to mental health problem, anxious was significantly related to social participation in elderly in rural area, while in urban area was isolated. This result implies that socio-demographic is an important factor of social participation in the elderly, and mental health contributes to their involvement. Some efforts are needed to maximize the social participation activities according to the characteristics of their environmental life.